2010
DOI: 10.1017/s1355617710000196
|View full text |Cite
|
Sign up to set email alerts
|

Rates of symptom reporting following traumatic brain injury

Abstract: This study examines rates of reporting of new or worse post-traumatic symptoms for patients with a broad range of injury severity at 1 month and 1 year after traumatic brain injury (TBI), as compared with those whose injury spared the head, and assesses variables related to symptom reporting at 1 year post-injury. Seven hundred thirty two TBI subjects and 120 general trauma comparison (TC) subjects provided new or worse symptom information at 1 month and/or 1 year post-injury. Symptom reporting at 1 year post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
202
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 306 publications
(211 citation statements)
references
References 54 publications
6
202
2
1
Order By: Relevance
“…While our mild group is likely more severely injured than those with mild TBI referred to in the literature, our rates of PTH with varying levels of severity of brain injury are similar and high. Our finding is consistent with the findings of a prior study which reported on rates of post-traumatic symptoms that included headache at 1 year in a prospectively studied group of participants with TBI with a broad range of TBI severity (Dikmen et al, 2010). Future studies will need to include similar definitions of TBI severity as well as headache in representative and non-select cases.…”
Section: Figsupporting
confidence: 90%
See 1 more Smart Citation
“…While our mild group is likely more severely injured than those with mild TBI referred to in the literature, our rates of PTH with varying levels of severity of brain injury are similar and high. Our finding is consistent with the findings of a prior study which reported on rates of post-traumatic symptoms that included headache at 1 year in a prospectively studied group of participants with TBI with a broad range of TBI severity (Dikmen et al, 2010). Future studies will need to include similar definitions of TBI severity as well as headache in representative and non-select cases.…”
Section: Figsupporting
confidence: 90%
“…H eadache is one of the most commonly reported symptoms following traumatic brain injury (TBI; Dikmen et al, 2010;Packard, 2005). Awareness of TBI-related symptoms, including headache, has increased as attention is focused on concussion or mild TBI sustained in sports injuries (Makdissi et al, 2010;Pellman et al, 2004), and as a result of the military conflicts in Iraq and Afghanistan (Hoge et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported mixed findings regarding the number of complaints and injury severity. Some studies found similar results demonstrating equal or higher levels of complaints in patients with mTBI compared to patients with moderate to severe TBI on the one hand (65,66). On the other hand, van der Horn, et al (67) found increasing symptom reporting with increasing brain injury severity.…”
Section: Discussionmentioning
confidence: 89%
“…Evidence clearly suggests that, for most people, the cognitive effects of mTBI resolve within days to three months post-injury (for meta-analyses see: Belanger et al, 2005;Frenchman et al, 2005;Schretlen & Shapiro, 2003). Yet, despite generally good long-term prognosis for individuals who experience a mTBI, a subset report the subjective experience of chronic cognitive deficits, especially in attention and memory (e.g., Dikmen, Machamer, Fann, & Temkin, 2010;Hartlage, Durant-Wilson, & Patch, 2001;Binder, Rohling, & Larrabee, 1997;Rimel, Giordani, Barth, Boll, & Jane, 1981).…”
Section: Prognosis and Recoverymentioning
confidence: 99%